Guidance of future geography teachers to active education for sustainable - Kolnik, Karmen (Journal for Geography, 2011)
Local, regional and national development plans and the various programs encroach upon the space is very often the case that the culture of public participation (so- called participatory culture) in Slovenia is weak and often divergent in advance. There is a lack of the awareness of the importance of public participation as a responsible role for the quality of each individual-oriented and the lack of the sustainable development. In this article we ask ourselves what is the role of geographical education in this area and we are representing a case of a teaching experimental work which was designed to train future geography teachers to active participatory learning. Having a selected sample of university students who are studying two subject programme of Geography and …... we examined some aspects of these realistic model of teaching education. The analysis of student seminar work performance, as becoming a future teachers of geography, has revealed how they mostly think about the environment (especially organic), and less on the economic, much less on the social aspects of sustainable development. Among the reasons for these situations for themselves, they indicate their prior empirical education.